Control interno y su incidencia en la gestión de inventarios de la empresa tabacalera “Tabace S.A.S”, del cantón El Empalme año 2022. - Peñarrieta Guerrero, Angie Gissela (2024)
The investigative project was focused on carrying out an internal control and its impact on inventory management of the Tabacalera “Tabace S.A.S” located in the canton of Empalme in 2022. This evaluation was carried out through COSO I, for this purpose the The objective approach is to analyze the impact of internal control on inventory management, evaluate the existing internal control system, examine the level of compliance with the applied standards, determine the degree of efficiency and effectiveness of inventory management, the research is It was framed in the field and documentary field, which has been based on the collection of bibliographic data, interviews and tools for the detection of information, inductive, deductive, quantitative and qualitative methods, along with techniques and instruments. Regarding the evaluation of internal control, the following results were obtained: confidence level of 75.56%, being moderate, therefore a risk level of 24.44%, was found, being low, referring to the risk measurement we have; inherent risk of 35.00%, this being high and the detection risk 10%, therefore, a control risk of 24.44% was obtained. The results of this internal control are detailed in specific reports for each evaluated process, which will provide the manager with the necessary information to correct situations that affect the operations of the tobacco company.